Molecular Epidemiology of Carbapenem-Resistant K. pneumoniae Clinical Isolates from the Adult Patients with Comorbidities in a Tertiary Hospital, Southern Saudi Arabia - Abdullah M. Alshahrani; Mutasim E. Ibrahim; Ahmed K. Aldossary; Mushabab A. Alghamdi; Omar B. Ahmed; Aref A. Bin Abdulhak (MDPI AG, 2022)
Hospitalized patients are likely to have chronic illnesses and are at an increased risk of mortality due to infection caused by MDR bacteria. We aimed to identify carbapenem-resistant genes carrying Klebsiella pneumoniae (K. pneumoniae) isolates and their risk factors recovered from adult patients with comorbidities. A cross-sectional study was carried out between April 2021 and December 2021 at King Abdullah Hospital (KAH) in Bisha province, Saudi Arabia. Seventy-one multi-drug resistant K. pneumoniae recovered from clinical samples and screened for carbapenemase genes of blaOXA-48-like, blaNDM-1, blaKPC, blaVIM, and blaIMP. Of 71 MDR K. pneumoniae examined, 47 (66.2%) isolates harbored various carbapenemase genes. The most prevalent single resistance gene was blaOXA-48-like (62.5%; n = 25), and 33.3% of them were recovered from sputum isolates. The blaNDM-1 gene was detected in 12 (30.0%) isolates, and eight of them were recovered from urine (n = 4) and blood (n = 4). Two (5.0%) single blaKPC genes were recovered from the sputum (n = 1) and blood (n = 1) isolates. In contrast, no blaIMP- and blaVIM-carrying isolates were detected. The co-existence of two resistance genes between blaOXA-48-like and blaNDM-1 was found in six strains, whereas only one strain was found to be produced in the three genes of blaNDM-1, blaKPC, and blaOXA-48-like. There were statistically significant associations between the presence of carbapenem-gene-carrying K. pneumoniae and patients' gender (χ2(1) = 5.94, p = 0.015), intensive care unit admission (χ2(1) = 7.649, p = 0.002), and chronic obstructive pulmonary disease (χ2(1) = 4.851, p = 0.028). The study highlighted the existence of carbapenemase-producing K. pneumoniae, particularly blaOXA-48-like and blaNDM-1, in patients with comorbidities. Our findings emphasize the importance of the molecular characterization of resistance-determinant-carrying bacterial pathogens as a part of infection control and prevention in hospital settings.